Elevated metabolic score for visceral fat was associated with increased prevalence of gallstones in American adults: a cross-sectional study - Lin, Hao; Shi, Kexuan; Luo, Shuang; Ye, Wu; Cai, Xiaoniao (Frontiers in Medicine, 2024)
Background: Metabolic Visceral Fat Score (METS-VF) recently introduced is posited to be a superior metric for assessing visceral adipose tissues (VAT) compared to traditional obesity indexes. This study aims to elucidate the correlation between METS-VF and the incidence of gallstones. Methods: In this cross-sectional study, the data from the National Health and Nutrition Examination Survey (NHANES) during the period from 2013 to 2020 were analyzed. And the correlation between METS-VF and the incidence of gallstones was explored through multivariate logistic regression analysis, receiver operating characteristic (ROC) curve, subgroup analysis and restricted cubic spline (RCS) regression. Results: This study included 5975 participants, of whom 645 (10.8%) were gallstone formers. As the quartile range of METS-VF increased, a notable rise in the prevalence of gallstones was observed (3.2% vs. 7.4% vs. 12.1% vs. 20.6%, p<0.001). Logistic regression analyses indicated a significant positive correlation between METS-VF and the risk of gallstones (OR=3.075, 95% CI: 2.158, 4.381). Subgroup analyses further revealed a stronger correlation between gallstones and METS-VF in subjects over 50 years old. RCS regression identified a non-linear positive correlation, with an inflection point at 6.698. Finally, the area under the ROC curve (AUC) of METS-VF was significantly larger (AUC=0.705, 95%: 0.685, 0.725) than those of traditional obesity indexes and other VAT surrogate markers. Conclusion: This study is the first to reveal a significant positive correlation between the prevalence of gallstones and METS-VF, with METS-VF outperforming other VAT surrogate markers in the diagnosis of gallstones.